Інформаційна функція авторських відступів в англомовних художніх прозових текстах - Архіпова, Ірина; Arkhipova, Iryna (Східноєвропейський національний університет імені Лесі Українки, 2015)
У роботі досліджено комунікативно-прагматичні характеристики авторських відступів в англо¬мовних художніх прозових текстах ХІХ–ХХ ст. Комунікативно-прагматичний підхід дав змогу виявити інформа¬ційний потенціал авторських відступів в англомовних художніх прозових текстах. This article focuses on revealing syntactic and pragmatic properties of author’s digression in English literary prose of the XIX–XX centuries. Author’s digression is determined as an autosemantic compositional unit of literary text, which ensures semantic relationship of different elements of the text, performs emotional and esthetic, phatic and cognitive functions, and is considered to be explicit means in defining the author’s and reader’s images. Lingual and cognitive approach made it possible to distinguish communicative functions of compositional and speech forms of author`s digression.
The Information Function of Author’s Digression in English Literary Prose
Keywords: автор; авторський відступ; інформаційна функція; образ автора; художній текст; author; author`s digression; author’s image; information function; literary text